2020
DOI: 10.26630/jk.v11i2.2051
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pola Makan, Tingkat Kecukupan Energi, dan Protein dengan Status Gizi pada Remaja

Abstract: Kebutuhan gizi remaja relatif besar karena remaja masih mengalami pertumbuhan dan umumnya melakukan aktivitas fisik lebih tinggi dibandingkan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
(2 reference statements)
1
1
0
7
Order By: Relevance
“…This result is corroborated by the distribution of variables that show the majority of children with adequate protein consumption patterns tend to have good nutritional status, namely 20 adolescents (47.6%). This finding is comparable to previous studies that showed there was a significant relationship between the level of protein deficiency and the nutritional status of respondents of SMP IT Iqra Kota Bengkulu in 2020 with p-value = 0.035 (18).…”
Section: The Relationship Of Protein Intake With Adolescent Nutrition...supporting
confidence: 88%
“…This result is corroborated by the distribution of variables that show the majority of children with adequate protein consumption patterns tend to have good nutritional status, namely 20 adolescents (47.6%). This finding is comparable to previous studies that showed there was a significant relationship between the level of protein deficiency and the nutritional status of respondents of SMP IT Iqra Kota Bengkulu in 2020 with p-value = 0.035 (18).…”
Section: The Relationship Of Protein Intake With Adolescent Nutrition...supporting
confidence: 88%
“…Hasil penelitian menunjukan ada hubungan pola makan, tingkat kecukupan energi, dan tingkat kecukupan protein dengan status gizi remaja. 13 Selain itu juga dihasilkan yang sama oleh hasil penelitian Serly (2015) tentang hubungan antara pola makan dengan status gizi pada remaja di Pondok Pesantren Nahdlatul Ulum Soreang Maros yang memiliki pola makan dan status gizi di peroleh nilai p-value =0,01 menunjukan, bahwa ada hubungan antara pola makan dengan status gizi remaja. Status gizi seseorang ditentukan berdasarkan asupan gizi dan kemampuan tubuh dalam menggunakan zatzat gizi.…”
Section: Pembahasan Hubungan Pola Makan Dengan Status Giziunclassified
“…Pola makan remaja dapat mempengaruhi status gizi remaja (Kumala et al, 2019). Remaja perempuan dengan status gizi normal memiliki pola makan yang baik, sedangkan remaja perempuan dengan status gizi tidak normal memiliki pola makan tidak baik (Margiyanti, 2021;, Utami et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified